2000
DOI: 10.1093/ps/79.11.1548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary T-2 fusariotoxin concentrations on the health and production of white Pekin duck broilers

Abstract: The effects of different dietary levels of T-2 toxin on production, biological, immunological, and pathological parameters of growing white Pekin ducks were studied to establish the "no effect" dietary concentration of, and "no effect" exposure time to, pure T-2 toxin. Day-old white Pekin ducks were randomly allotted to nine groups of 10 ducks each. One group served as a control, and no mycotoxin was added to its feed. The feeds of the experimental groups were supplemented with 0.2, 0.4, 0.6, 0.8, 1.0, 2.0, 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 41 publications
2
23
0
1
Order By: Relevance
“…Even though the inconsistency with EU Commission guidance values took place in case of 24 samples only, it should be taken into account, that the values are set for single compounds. Moreover, possible productivity and animal health problems connected with mycotoxins present in feed at levels lower than those set by the European Commission have been pointed out before (Rafai et al, 2000;Obremski et al, 2008;Yunus et al, 2012;Grenier and Applegate, 2013). With a view to the fact, that 60% of the complete feed samples as well as 70% of the maize silage samples delivered by veterinary doctors and farmers were examined following some breeding problems, and that other factors' influence had been eliminated, it may be assumed, that the problems could have been associated with the mycotoxins, even though their levels were below the guidance values given by the EU.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the inconsistency with EU Commission guidance values took place in case of 24 samples only, it should be taken into account, that the values are set for single compounds. Moreover, possible productivity and animal health problems connected with mycotoxins present in feed at levels lower than those set by the European Commission have been pointed out before (Rafai et al, 2000;Obremski et al, 2008;Yunus et al, 2012;Grenier and Applegate, 2013). With a view to the fact, that 60% of the complete feed samples as well as 70% of the maize silage samples delivered by veterinary doctors and farmers were examined following some breeding problems, and that other factors' influence had been eliminated, it may be assumed, that the problems could have been associated with the mycotoxins, even though their levels were below the guidance values given by the EU.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NH 3 and RH in a poultry house had an additive detrimental effect on the proliferation of lymphocytes. It was reported that other types of stressors also decreased the proliferation of lymphocytes (Rafai et al, 2000;Swamy et al, 2004;Long et al, 2011). In chickens, it is well known that stress status is associated with increased plasma corticosterone concentrations because corticosterone is the end product of the hypothalamic-pituitary-adrenal (HPA) axis.…”
Section: Discussionmentioning
confidence: 99%
“…The production of antibodies can also be impaired (Niyo et al, 1988;Kamalavenkatesh et al, 2005;Li et al, 2006a,b). Furthermore, T-2 toxin reduces lymphocyte proliferative response (Rafai et al, 1995b(Rafai et al, , 2000Kamalavenkatesh et al, 2005) and disturbs the maturation process of dendritic cells (Blaylock et al, 1993;Hymery et al, 2006).…”
Section: Introductionmentioning
confidence: 99%